Pre-distortion technique to improve linearity of low noise amplifier. (March 2017) - Jafarnejad, Roya; Jannesari, Abumoslem; Sobhi, Jafar
Abstract: A novel technique to improve the linearity of Low Noise Amplifier (LNA) based on pre-distortion in the input matching circuit is proposed. The linearization technique is applied to a Capacitive Cross Coupled Common Gate (CCC-CG) structure. An auxiliary transistor operating in weak inversion region is used to adjust the input matching circuit nonlinearity. It has been shown that the nonlinearity of input matching circuit can efficiently compensate the nonlinearity of transconductance ( G m ) of the amplifier, and improves the third Input Intercept Point (IIP3). Furthermore, the added transistor is used in a feedback path which provides a noise canceling scheme. Thus, linearity improvement is achieved in addition to low Noise Figure (NF). Post-layout simulation results in TSMC 0.18 µm CMOS technology, show a gain of 18.55 dB with an upper −3 dB frequency of 2.96 GHz, the minimum NF equals to 2.63 dB and IIP3 of 11 dBm, while consuming 2.77 mA from a 1.5 V supply. Highlights: In this paper a new technique based on pre-distortion in the input matching circuit is proposed to improve the linearity of Low Noise Amplifier (LNA). A Capacitive Cross Coupled Common Gate based LNA with high linearity is presented based on the proposed idea. Besides pre-distortion performance, the auxiliary transistor forms a noise canceling scheme and partially cancel out the channel thermal noise of main amplifying transistor. The circuit is inductoreless and suitable for wideband low power applications.